Factors Associated with Acute Malnutrition among Children Admitted to a Diarrhoea Treatment Facility in Bangladesh - Connor Fuchs; Tania Sultana; Tahmeed Ahmed; M. Iqbal Hossain (International Journal of Pediatrics)
To assess the risk factors for acute malnutrition (weight-for-height z-score (WHZ) < −2), a case-control study was conducted during June–September 2012 in 449 children aged 6–59 months (178 with WHZ < −2 and 271 comparing children with WHZ ≥ −2 and no edema) admitted to the Dhaka Hospital of icddr,b in Bangladesh. The overall mean ± SD age was 12.0 ± 7.6 months, 38.5% (no difference between case and controls). The mean ± SD WHZ of cases and controls was −3.24 ± 1.01 versus −0.74 ± 0.95 (P<0.001), respectively. Logistic regression analysis revealed that children with acute malnutrition were more likely than controls to be older (age > 1 year) (adjusted OR (AOR): 3.1, P=0.004); have an undernourished mother (body mass index < 18.5), (AOR: 2.8, P=0.017); have a father with no or a low-paying job (AOR: 5.8, P<0.001); come from a family having a monthly income of <10,000 taka, (1 US$ = 80 taka) (AOR: 2.9, P=0.008); and often have stopped predominant breastfeeding before 4 months of age (AOR: 2.7, P=0.013). Improved understanding of these characteristics enables the design and targeting of preventive-intervention programs of childhood acute malnutrition.